Visualising war / peace photographs - Elareshi, Mokhtar (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2024)
This study analyses the visual coverage of the 2022 Russian-Ukrainian conflict on Asian news sites, utilising the frameworks of war and peace journalism. Conducting a content analysis of 397 images from seven leading Asian news sites, we contribute to the literature on visual coverage, particularly from online platforms. Our analysis identifies the predominant visual narratives employed by these news sites and offers insights into variations in coverage intensity, regional and ethnic focuses, portrayal of age groups, and depiction of harm. The study extends the understanding of framing theory by analysing visual frames, providing valuable implications for future visual studies and contributing to a deeper understanding of conflict portrayal in online news media.
Keywords: Asian news sites; azijske novičarske spletne strani; conflict coverage; media representation; medijska reprezentacija; mirovno novinarstvo; peace journalism; pokrivanje konfliktov; rusko-ukrajinski konflikt; Russian-Ukrainian conflict; visual coverage; vizualna pokritost; vojno novinarstvo; war journalism